Lowland tundra plant stoichiometry is somewhat resilient decades following fire despite substantial and sustained shifts in community structure. Issue 1 (31st December 2022) - Baillargeon, Natalie; Pold, Grace; Natali, Susan M.; Sistla, Seeta A.
ABSTRACT: The Arctic is experiencing the greatest increase in average surface temperature globally, which is projected to amplify wildfire frequency and severity. Wildfire alters the biogeochemical characteristics of arctic ecosystems. However, the extent of these changes over time—particularly with regard to plant stoichiometries relative to community structure—is not well documented. Four years after the Yukon-Kuskokwim Delta, Alaska, experienced its largest fire season, aboveground plant and lichen biomass was harvested across a gradient of burn history: unburned ("reference"), 2015 burn ("recent burn"), and 1972 burn ("historic burn") to assess the resilience of tundra plant communities to fire disturbance. Fire reduced aboveground biomass in the recent burn; early recovery was characterized by evergreen shrub and graminoid dominance. In the historic burn, aboveground biomass approached reference conditions despite a sustained reduction of lichen biomass. Although total plant and lichen carbon (C) and nitrogen (N) were reduced immediately following fire, N stocks recovered to a greater degree—reducing community-level C:N. Notably, at the species level, N enrichment was observed only in the recent burn. Yet, community restructuring persisted for decades following fire, reflecting a sustained reduction in N-poor lichens relative to more N-rich vascular plant species.